Sea level acceleration under the magnifier - İz H. Bâki (Sciendo, 2021)
Detection and quantification of sea level accelerations at tide gauge stations are needed for assessing anthropogenic contributions to the climate change. Nonetheless, uniform or non-uniform sea level accelerations/decelerations are particularly di˚cult to discern partly because of their small magnitudes and partly because of the low frequency sea level variations as confounders. Moreover, noisy excursions in the observed sea level variations also exacerbate reliability of estimated sea level accelerations. This study explores the uniformity of a sea level acceleration graphically that is left unmodeled in the residuals of a least squares solution using cumulative sum charts. Key West, USA tide gauge station’s record is studied for a demonstration. The cumulative sum charts of the residuals of a rigorous kinematic model solution without the acceleration parameter revealed its crisp and uniform signature experienced at this station since 1913.